Shared and Unique Features of Human Interferon-Beta and Interferon-Alpha Subtypes - Wittling, Megen C.; Cahalan, Shannon R.; Levenson, Eric A.; Rabin, Ronald L. (Frontiers in Immunology, 2021)
Type I interferons (IFN-I) were first discovered as an antiviral factor by Isaacs and Lindenmann in 1957, but they are now known to also modulate innate and adaptive immunity and suppress proliferation of cancer cells. While much has been revealed about IFN-I, it remains a mystery as to why there are 16 different IFN-I gene products, including IFNβ, IFNω, and twelve subtypes of IFNα. Here we discuss shared and unique aspects of these IFN-I in the context of their evolution, expression patterns, and signaling through their shared heterodimeric receptor. We propose that rather than investigating responses to individual IFN-I, these aspects are the foundation for an alternative approach towards investigating roles for IFNα subtypes. Finally, we review uses of IFNα and IFNβ as therapeutic agents to suppress chronic viral infections or to treat multiple sclerosis.